2023
DOI: 10.1001/jamanetworkopen.2023.4059
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Use of Oral Anticoagulants for Adults With Venous Thromboembolism in the US, 2010-2020

Abstract: ImportanceThe introduction of direct oral anticoagulants (DOACs) has transformed the treatment of venous thromboembolism (VTE). Large health care databases offer valuable insight into how oral anticoagulants (OACs) are used in clinical practice and may aid in understanding reasons for changes in therapy.ObjectivesTo evaluate prescribing patterns of OACs for patients with VTE and identify clinical events that precede treatment changes.Design, Setting, and ParticipantsThis retrospective cohort study used data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
(36 reference statements)
2
2
0
Order By: Relevance
“…Our study findings are aligned with the existing literature, showing a decline in warfarin use in favour of DOACs in the general AF population, 28–30 and generally consistent with the limited available literature examining AF patients with CKD. A prior study examining anticoagulant use in newly admitted nursing home residents with AF and CKD (2011–2018) noted a clear preference for warfarin among patients with CKD compared with those without CKD 31 ; whereas, our study found a more modest difference in warfarin use between patients with CKD and non-CKD.…”
Section: Discussionsupporting
confidence: 91%
“…Our study findings are aligned with the existing literature, showing a decline in warfarin use in favour of DOACs in the general AF population, 28–30 and generally consistent with the limited available literature examining AF patients with CKD. A prior study examining anticoagulant use in newly admitted nursing home residents with AF and CKD (2011–2018) noted a clear preference for warfarin among patients with CKD compared with those without CKD 31 ; whereas, our study found a more modest difference in warfarin use between patients with CKD and non-CKD.…”
Section: Discussionsupporting
confidence: 91%
“…Our study findings are generally consistent with the available literature on the general trends in DOAC use in the US and globally . A Medicare study of older data from 2012 to 2014 found that Black patients had 25% lower odds of initiating DOACs compared with White patients, whereas Hispanic patients exhibited similar odds .…”
Section: Discussionsupporting
confidence: 90%
“…26 Our study findings are generally consistent with the available literature on the general trends in DOAC use in the US and globally. 12,14,[27][28][29][30] A Medicare study of older data from 2012 to 2014 found that Black patients had 25% lower odds of initiating DOACs compared with White patients, whereas Hispanic patients exhibited similar odds. 14 Another investigation of 12 417 patients with AF who were 21 years or older in the Outcomes Registry for Better Informed Treatment of Atrial Fibrillation II registry from 2013 to 2016 found that Black patients were 40% less likely to use DOACs compared with White patients.…”
Section: Discussionmentioning
confidence: 99%
“…5 After the US Food and Drug Administration approved DOACs for the secondary prevention of VTE, DOACs quickly overtook warfarin as the most commonly initiated oral anticoagulants for VTE, and the American Society of Hematology currently recommends DOACs as the treatment of choice for VTE. 6,7 While studies comparing VTE patients' mortality and PE risk show DOACs do not provide an advantage over warfarin, DOACs do not require the INR monitoring, dietary restrictions, and dose adjustments required in warfarin use. 7 Overall failure rates of anticoagulation with DOACs are low, with failure being more common in patients with a hypercoagulable condition such as malignancy and antiphospholipid syndrome as well as in patients with mechanical heart valves.…”
Section: Case Presentationmentioning
confidence: 99%